Reaching Out: The Basque Transnational Body in the Poetry of Kirmen Uribe - Enrique Álvarez; Ester Hernández-Esteban (Studies in 20th & 21st Century Literature, 2020)
In this paper we explore the contribution of Kirmen Uribe, a Basque writer, artist and cultural activist, to the process of political reconciliation in the Basque country, a socially transforming compromise brought about by the dissolution of the Basque terrorist organization ETA in October 20th, 2011. Uribe achieved literary recognition and public notoriety within the Iberian cultural landscape with the publication of his novel Bilbao-New York-Bilbao in 2008, for which he received the Spanish National Literature Prize for Narrative in the following year. However, we argue that it is with his earlier collection of poems Bistatean Heldu Eskutik ‘Meanwhile Take my Hand,’ originally published in Euskara—the Basque language—in 2001, that Uribe initiates a strong, symbolic act towards reconciliation in Basque social relations. Using a methodological framework built on the juxtaposition of transnational and affect studies, we analyze the transformational thrust of an affective, reconciliatory language in Uribe’s poems. Building on Deleuze and Guattari’s notion of a minor literature, we first consider how this affective language overflows and deterritorializes the traditional geographical and discursive boundaries of Basque cultural nationalism; then, we analyze the production of Uribe’s poetic expression within a specific temporality, in which Basque society demanded the end of violence in the Basque country; and, finally, we argue that this poet’s self-conscious poetics of affect provides a cultural model for the democratization of the Basque social body reterritorialized in the transnational realm.
Keywords: Basque Poetry; Iberian Cultural Studies; Affect; Transnationalism